Genetic mapping and characterization of the bleeding disorder in the fawn-hooded hypertensive rat - Datta, Yvonne H.; C.Wu, Francisca; Dumas, Pierre C.; Rangel-Filho, Artur; Datta, Milton W.; Ning, Gang; Cooley, Brian C.; Majewski, Rebecca R.; Provoost, Abraham P.; Jacob, Howard J. (Thrombosis and Haemostasis, 2003)
Release of platelet dense granule contents occurs in response to vascular injury, playing an important role in platelet aggregation and primary hemostasis. Abnormalities of the platelet dense granules results in a bleeding disorder of variable severity termed “storage pool defect” (SPD). We have examined the fawn-hooded hypertensive (FHH) rat as a model of SPD in order to genetically map the locus (Bd) responsible for prolonged bleeding. Platelet function assays of the FHH rat confirmed the presence of a platelet dense granule SPD. However electron microscopy and lysosomal enzyme assays indicated differences between the FHH rat and other rodent models of SPD. Genetic mapping through the use of congenic FHH rats localized the Bd locus to an approximately 1 cM region on rat chromosome 1. Through the use of comparative mapping between species and analysis of the initial draft of the rat genome assembly, six known and thirty-four putative genes were identified in the Bd locus. None of these genes have been previously implicated in platelet function. Therefore positional cloning of the gene responsible for the bleeding disorder in the FHH rat will lead to new insights in platelet physiology, with implications for diagnosis and management of hemostatic and thrombotic disorders.
Keywords: Platelets; dense granules; storage pool defect; rats; genetic mapping